Implementation of quality tools in small medium industry - Mirzan Aidif, Mohd Shakhir (2008)
Quality tools are one of the methods used to control and improve productivity by many ways such as reducing the repetitive mistake. Quality plays such an important role in the manufacturing industry in order to raise the profit of the company and also the company’s name. SMI has many problems in their company specifically in the processing line. This is because they just focusing in producing the products and not taking the lack occur in the processing very well. This study is about to apply the quality tools in the processing line in order to identify where the highest waste is occur at and to give suggestion for improvement at the major waste involves in the processing line. The selected SMI is producing spice which is one of important ingredients in Malaysian food. There are four stages for producing spice, weighing, roasting, grinding and packaging. Due to the interview there are two causes contribute to waste, which are roasting and grinding process. From the data taken and the analysis done, it shows the highest waste occur in the grinding process which cause by four factors, expose to the moving fan, spices stick at the grind blade, rotating gear and tupperware without lid. This shows that quality tools managed to find the highest waste occur in the processing line. The company can reduce the waste by put on the lid on the table used for cooling the spice, service the grinding blade once after running three time to avoid the wet spices will attract more spices to stick together, build a compartment at the rotating gear as obstacle and put on the lid on the tupperware to ensure the spice will not getting away from the tupperware.